Does the Fifth Industrial Revolution and Corporate Governance Matter? An Investigation of the Top 100 PSX Companies (Journal of Asian Development Studies, 2025)
With the help of modern technologies and performances of good governance, business performance could be improved. This research examines the relationship between corporate governance (CG) mechanisms and technological use to the financial performance (FP) of the 100 listed firms on the PSX for six years from 2018 to 2023. Based on agency theory and resource based view, we look at specific governances such as board size (BS), board diversity (BS), Audit committee independence (ACI) and risk management (RM) policies and practices, and the implementation of Industrial Revolution 5.0 skills such as AI Robotics and Automation. Through the application of the Generalized Method of Moments (GMM) model, any endogeneity is dealt with, and financial performance embraces Return on Assets (ROA) and Return on Equity (ROE). The findings indicate that BD, the ACI, and technology adoption positively affect the performance. Nevertheless, its value is adversely affected by the level of Financial Leverage (LEV). Although it is critical, risk management exhibits low impact level. The study's findings hold when using different model configurations and diagnostic tests, such as the Arellano-Bond tests on autocorrelation and the Hansen tests on the instruments' relevance. The research provides a knowledge base of CG and technology and real-world implications for firms to improve governance systems and advanced technologies to improve their financial performance.